Transcutaneous electrical nerve stimulation reduces acute pain, and the use of analgesics after ankle fracture surgery - da Rocha Macedo, Rafael; de Souza Ferreira, Aleksandro; Morais de Oliveira Silva, Ícaro; Lamartine Nogueira Duarte, Matheus; Gave Lima, Ricardo Luiz; Finizola, Elzir; Asaumi, Inácio Diogo; Miller Reis Rodrigues, Luciano; Yukio Ikemoto, Roberto (Journal of the Foot & Ankle, 2022)
Objective: To evaluate the applicability of transcutaneous electrical nerve stimulation (TENS) as a complementary treatment method to non-opioid analgesics for acute postoperative pain in patients undergoing surgical treatment due to ankle fractures. Methods: A prospective, randomized, analytical, cross-sectional study performed after ankle fracture surgery. Two groups were randomized as follows: group 1 (Intervention) received TENS and non-opioid analgesic (dipyrone), and group 2 (Control) received non-opioid analgesic (dipyrone). Results: This study demonstrated that TENS in patients undergoing surgical treatment of ankle fractures reduces the use of rescue opioids significantly to control postoperative pain. Conclusion: TENS devices may be another safe option to control postoperative pain and reduce the use of opioids, avoiding adverse effects from this class of analgesic. Level of Evidence II; Therapeutic Studies; Prospective Comparative Study.